Coordination Assisted Distal C−H Alkylation of Fused Heterocycles. (15th August 2019) - Ramakrishna, Kankanala; Biswas, Jyoti Prasad; Jana, Sadhan; Achar, Tapas Kumar; Porey, Sandip; Maiti, Debabrata
Abstract: Distal C−H bond functionalization of heterocycles remained extremely challenging with covalently attached directing groups (DG). Lack of proper site for DG attachment and inherent catalyst poisoning by heterocycles demand alternate routes for site selective functionalization of their distal C−H bonds. Utilizing non‐productive coordinating property to hold the heterocycle into the cavity of a template system in a host–guest manner, we report distal C−H alkylation (C‐5 of quinoline and thiazole, C‐7 of benzothiazole and benzoxazole) of heterocycles. Upon complexation with heterocyclic substrate, nitrile DG in template directs the metal catalyst towards close vicinity of the specific distal C−H bond of the heterocycles. Our hypothesized pathway has been supported by various X‐ray crystallographically characterized intermediates. Abstract : Fernweh : Die C‐H‐Fernalkylierung (C5 des Chinolins und Thiazols, C7 des Benzothiazols und Benzoaxazols) von Heterocyclen wird vorgestellt. Nach Komplexierung mit dem heterocyclischen Substrat lenkt Nitril‐DG im Templat den Metallkatalysator in die Nähe der spezifischen fernen C‐H‐Bindung des Heterocyclus. Der angenommene Pfad wird durch verschiedene mit Röntgenkristallographie charakterisierte Intermediate unterstüzt.